Efektivitas Media Audiovisual dan Leaflet tentang Perilaku Seksual Pranikah terhadap Pengetahuan dan Sikap Remaja - Siti Rochmaedah; Mariyati Mardjuky; Ira Sandi Tunny; Denicell P. Tetelepta (Pusat riset dan Inovasi Nasional, 2026)
Physiological changes in adolescents during the transition period, both biologically, cognitively, psychosexually, and psychosocially, are very vulnerable to various risky behaviors such as premarital sexual behavior, abortion, unwanted pregnancy, STIs, and drug use. One effort to increase adolescent awareness about premarital sex is health education. This study identified the effectiveness of audiovisual media and leaflets about premarital sexual behavior on the knowledge and attitudes of adolescents at SMA Negeri 20 Seram Bagian Barat. The study used a quasi-experimental approach, pre-post-test control group design, with 40 samples. The Wilcoxon test results for the intervention group showed a p-value of 0.001 (p < 0.05), indicating a significant difference in adolescent knowledge and attitudes before and after health education using audiovisual media. The control group showed a p-value > 0.05, indicating no significant difference in adolescent knowledge and attitudes before and after health education using leaflets. The Man-Whitney test results showed a p-value < 0.000 (p value < 0.05) for the intervention group post-test. It was concluded that there was a significant difference in health education using audiovisual media and leaflets regarding premarital sexual behavior on adolescent knowledge and attitudes at State Senior High School 20, West Seram.